Association Between Perceived Stress with Anxiety, Depression, and Resilience in Hemodialysis Patients During Coronavirus Disease 2019 Pandemic - Esra Aydin Sunbul; Dilek Barutcu Atas; Gulcin Kantarcı (Turkish Journal of Nephrology)
Background: Research has revealed heightened levels of anxiety, depression, and stress in various groups during the coronavirus disease 2019 (COVID-19) pandemic. Nevertheless, the infuence of the pandemic on the mental well-being of individuals undergoing dialysis has yet to be fully understood. The aim of this study was to investigate the association between perceived stress (PS) with anxiety, depression, and resilience in hemodialysis patients during COVID-19 pandemic.